Analisis Aspek Pembiayaan Untuk Mendukung Sektor Kemaritiman yang Berwawasan Lingkungan di Indonesia - Sujai, Mahpud (Bumi Lestari, 2019)
Maritime sector is an advance development priority of the current government. Various development programs such as coastal communities and borders empowerment, maritime infrastructure development, increased production of marine fisheries and the maritime conservation has become important program priorities. However, in implementing these programs, financing and budgetary aspects remained a major constraint both in central and local government. Therefore, various breakthroughs and alternative sources of financing are needed to support the development of environmentally maritime sector. The purpose of this study is to explore the various aspects of financing that can be promoted by the stakeholders , including the government in addressing the issue of budget constraints for the development of maritime sector. Methodology that will be used in this research is descriptive analysis that will explore various alternative sources of financing as well as benchmark analysis of both cross countries analysis and cross sectoral analysis . This study is expected to provide recommendations for stakeholders , especially the government in creating a new alternative sources of financing to support the development of environmentally maritime sector.